Pre-operative administration of butorphanol mitigates emergence agitation in patients undergoing functional endoscopic sinus surgery: A randomized controlled clinical trial - Zhang, Xiao; Qi, Siyi; Lin, Zhen; Zhang, Yizhe; Dai, Wanbing; Tian, Weitian; Tian, Jie; Zheng, Li; Su, Diansan; Huai, Xiaorong (Frontiers in Psychiatry, 2023)
Background: This study explored the effectiveness of preoperative intravenous injection of butorphanol in the alleviation of emergence agitation (EA) in patients undergoing functional endoscopic sinus surgery (FESS). Methods: Patients (n = 708) were randomized into two groups. The butorphanol group (Group B, n = 358) received butorphanol infusion (20 ug/kg) before anesthesia induction, while the control group (Group C, n = 350) received an equal volume of normal saline infusion. General anesthesia was induced with sufentanil, propofol and rocuronium, and was maintained with sevoflurane and remifentanil. Vasoactive drugs maintained the haemodynamic indices within 20% of the baseline. Results: The incidence of EA was significantly lower in Group B than that in Group C (Group B vs. C: 24.3% vs. 31.4%, respectively; P = 0.034). The times to spontaneous breathing (26.5 min vs. 23.7 min, P = 0.011), verbal response (36.0 min vs. 33.4 min, P = 0.012), and extubation (31.0 min vs. 28.7 min, P = 0.025) were longer in Group B, and the grade of cough (0.33 vs. 0.43, P = 0.024) at extubation in Group B was lower than that in Group C (P = 0.024). The mean arterial pressure at the end of the operation (P = 0.004) and at 5 min after extubation (P = 0.008) was higher and hypotension was less prominent (0.6% vs. 2.6%, P = 0.030) in Group B. Conclusions: Preoperative intravenous injection of butorphanol decreased the incidence of EA after FESS and provided smooth and haemodynamically stable emergence without extending the stay in postanesthesia care unit.